Identifikasi dan Perilaku Nyamuk Anopheles di Kulon Progo: Identification and behavior of Anopheles mosquitoes in Kulon Progo - Astuti, Fardiasih Dwi; Hermayanti, Shafira Putri; Sukamto, Ali (Perkumpulan Entomologi Kesehatan Indonesia, 2025)
Abstract Identifying and characterizing Anopheles mosquitoes through spot surveys is critical for malaria control, especially in endemic and receptive areas. In the Special Region of Yogyakarta, Indonesia, malaria cases have been reported in Kulonprogo, with the latest 10 cases in 2023. This study aimed to identify Anopheles species and their resting behavior as risk factors for local malaria transmission. A cross-sectional entomological survey was conducted in Samigaluh, Kulonprogo. Mosquitoes were collected using human landing catches (indoor and outdoor) and resting collections in animal shelters from 6:00 PM to 6:00 AM. Specimens were identified by species, vector density, and parity status. Five Anopheles species were detected, predominantly resting in animal shelters: An. vagus (71.9%), An. annularis (21.9%), An. aconitus (3.95%), An. kochi (1.69%), and An. barbirostris (0.56%). All biting activity occurred outdoors between 6:00 PM and 3:00 AM, with species-specific activity peaks. An. vagus had the highest man biting rate (0.88 bites/person/hour) and was active early in the evening. The overall parity rate was 85.71%, indicating a mature mosquito population with potential for malaria transmission. These findings highlight An. vagus as the dominant species in the area, exhibiting exophagic and zoophilic behavior, and suggest that sustained vector surveillance is essential to support malaria elimination efforts in receptive regions.